017 Any Qualified Provider - A positive experience for a hospice Lymphoedema service. (1st October 2013) - Stevens, Alison; Sueur, Janet Le
Abstract : Background/context: Historically the hospice had provided a lymphoedema service for patients who had predominantly cancer related lymphoedema. However, over time it became apparent that the condition for many of these patients had stabilised and they were living with chronic lymphoedema. This posed a dilemma for the hospice as to whether hospice funds should continue to be used to treat this category of 'non-palliative' patients. The hospice undertook a detailed activity analysis of the lymphoedema service and presented this to the NHS commissioning managers. This led to the hospice working with one PCT area to establish an NHS community based non-palliative lymphoedema service. A further, newly formed CCG decided to take a different route to offer a non-palliative service under an Any Qualified provider (AQP) contract. Aim: To establish a non-palliative lymphoedema service under an AQP contract as an extension to the existing experienced hospice lymphoedema service. Approach used Hospice managers attended AQP stakeholder meeting. Submission of tender documentation. Acceptance of contract. Redesign of current service to accommodate new contract for wider geographical area. Recruitment, training of additional staff. Set up of data collection to meet requirements of contract. Setting up good working relationships with the other 3 commissioned AQP providers. Outcomes: Patients who are classed as non-palliative have the benefit of an excellent well established palliative lymphoedema service. Application to hospice practice. The hospice now receives full funding for non-palliative patients. The hospice lymphoedema team are able to access additional training and gain knowledge of different conditions, this ultimately extends the range of skills and experience that they have to hand to support palliative patients. Non-palliative patients more prepared to accept hospice care should they have further disease recurrence or their condition deteriorates. Opportunity for hospice managers to gain experience in AQP commissioning process.